Evaluación Zoometrica De Bovinos Bon Y Romosinuano Como Modelo De Gestión De La Información Para Asocriollo (Actividades Realizadas En Trabajo De Grado Como Pasantía En Ganaderías De Asocriollo) (2023)
This document presents the results of the Zoometrics carried out on Blanco orejinegro (BON) and Romosinuano cattle in livestock farms associated with Asocriollo, within the activities proposed within the framework of the agreement made with the UAN, and carried out for the subject Degree Work in the Internship option.